Design of a MUC1-based tricomponent vaccine adjuvanted with FSL-1 for cancer immunotherapy. Issue 12 (24th July 2019) - Li, Mingjing; Wang, Zhaoyu; Yan, Bocheng; Yin, Xiaona; Zhao, Yue; Yu, Fan; Meng, Meng; Liu, Yonghui; Zhao, Wei
Abstract : The designed tricomponent MUC1-based vaccine induced robust immune responses and exhibited a significant reduction in tumor burden. Abstract : MUC1 is an attractive target for cancer vaccines as a result of its over-expression and aberrant glycosylation pattern on many tumor cells. However, the low immunogenicity of MUC1 and immune tolerance have limited its application. Herein, we designed MUC1-based tricomponent antitumor vaccines adjuvanted with fibroblast stimulating lipopeptide 1 (FSL-1). Immunological results indicate that the glycosylated tricomponent vaccine candidate has elicited both humoral and cellular immune responses. The induced antibodies could effectively bind to MCF-7. Furthermore, the vaccine exhibited an obvious reduction in tumour burden.